2009
DOI: 10.1002/ajim.20783
|View full text |Cite
|
Sign up to set email alerts
|

Back problems among emergency medical services professionals: The LEADS health and wellness follow‐up study

Abstract: This study indicated that work-life, health, and demographic characteristics of EMS professionals were associated with reporting recent back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
1
14
0
6
Order By: Relevance
“…25 In contrast, approximately half (50.5%) of a large American paramedic sample (n = 930) reported having pain for one or more days in a 2-week period. 26 In an American sample of urban firefighters (n = 382), approximately 13% reported pain occurring often or frequently within the prior week. 27 Finally, a qualitative study of 17 American 911 dispatchers evidenced reports of somatic concerns, including chronic pain, as being common among dispatchers.…”
Section: Introductionmentioning
confidence: 99%
“…25 In contrast, approximately half (50.5%) of a large American paramedic sample (n = 930) reported having pain for one or more days in a 2-week period. 26 In an American sample of urban firefighters (n = 382), approximately 13% reported pain occurring often or frequently within the prior week. 27 Finally, a qualitative study of 17 American 911 dispatchers evidenced reports of somatic concerns, including chronic pain, as being common among dispatchers.…”
Section: Introductionmentioning
confidence: 99%
“…As part of their job ambulance workers perform many tasks that expose them to musculoskeletal risks including adopting awkward postures (Doormal et al, 1995;Ferreira and Hignett, 2005), moving patients from a bed/trolley to a stretcher (Lavender et al, 2000); and transporting patients down stairs (Studnek et al, 2010;Arial et al, 2014). In 2003 Hignett et al reported a systematic literature review on patient handling activities across healthcare sectors including three studies of moderate quality which found that ambulance work can result in harmful working postures (in particular over reaching/over stretching), with the highest risk tasks involving transportation of patients (Doormal et al, 1995;Furber et al, 1997;Massad et al, 2000).…”
Section: Manual Handling Risksmentioning
confidence: 99%
“…No que se refere aos fatores de risco para as DOM, seis estudos mencionam esses fatores, dentre eles: a idade 14,18 , o sexo 14 , a escolaridade 17 , a aptidão física 18 , a atividade profissional 14,18,19 , o trabalho noturno 15,16 , a duração do período de trabalho, o trabalho em turnos consecutivos e horas de recuperação 15 , a saúde geral autorrelatada 17 e a satisfação com o trabalho 18 . Ao analisarmos a força de evidência desses fatores de risco, obteve-se nível "forte" para idade e atividade profissional; "limitado" para escolaridade, aptidão física, saúde geral e satisfação com trabalho; e "sem evidência" para os demais fatores de risco.…”
unclassified
“…Os demais fatores que apresentaram limitado nível de evidência foram investigados em apenas um estudo e por isso restringem discussões aprofundadas, como é o caso da satisfação do trabalho, da aptidão física, da escolaridade e da saúde em geral. Resumidamente, com os dados que se tem até o momento, profissionais insatisfeitos com a sua atribuição 18 , com pior aptidão física 18 e que relatavam saúde ruim 17 eram significativamente mais propensos a relatar problemas nas costas. Além disso, indivíduos com maior nível de escolaridade foram menos propensos a relatar dor nas costas 17 .…”
unclassified
See 1 more Smart Citation